Novel cutting inserts with multi-channel irrigation at the chip-tool interface: Modelling, design and experiments. Issue 1 (2020) - Liao, Zhirong; Xu, Dongdong; Axinte, Dragos; M'Saoubi, Rachid; Thelin, Jimmy; Wretland, Anders
Abstract: The friction at chip-tool interface can considerably affect the chip formation and consumed energy during cutting of superalloys. However, it is difficult to deliver the lubricant to the chip-tool interface to reduce the friction effect. Thus, this paper proposed a novel solution of insert design by locating macro-channels on the rake face which connect with the micro-channels for irrigating the coolant into the chip-tool interface, while considering the cooling and lubricating efficiency. A significant reduction of tool wear, cutting force and specific cutting energy has been demonstrated, while an improved chip fragmentation as well as microstructure has also been achieved.